(untitled) (Eurasian Journal of Ecology, 2016)
Examine the contents of heavy metals in the water of the river Belaya in the territory of Beloretsk district, Republic of Bashkortostan. Identified the excess of average annual concentrations of Cu, Zn, Fe, Mn respect to the prescribed limit values.